Epigallocatechin Gallate Relieved PM2.5-Induced Lung Fibrosis by Inhibiting Oxidative Damage and Epithelial-Mesenchymal Transition through AKT/mTOR Pathway. (6th June 2022) - Zhongyin, Zhou; Wei, Wang; Juan, Xiong; Guohua, Fan
Abstract : Oxidative damage and epithelial-mesenchymal transition (EMT) are main pathological processes leading to the development of PM2.5-induced lung fibrosis. Epigallocatechin gallate (EG), a natural polyphenol extracted from green tea, possesses the ability to combat oxidative stress and inflammation. However, the potential roles of EG in PM2.5-induced lung fibrosis have not been reported yet. In the present study, we investigated whether EG could relieve PM2.5-induced lung injury and fibrosis in vivo and in vitro . To mimic PM2.5-induced lung fibrosis, C57/BL6 mice were intranasally instilled with PM2.5 suspension, and MLE-12 lung epithelial cells were stimulated with PM2.5 (100 μ g/mL) in vitro . The results showed that intragastric administration of EG (20 mg/kg/d or 80 mg/kg/d for 8 weeks) significantly prevented lung injury, inflammation, and oxidative stress in PM2.5-induced mice, apart from inhibiting collagen deposition. Additionally, EG treatment also suppressed the activation of AKT/mTOR signaling pathway in lung tissues challenged with PM2.5. In vitro experiments further demonstrated that EG treatment could enhance cell viability in a concentration-dependent manner in PM2.5-treated MLE-12 lung epithelial cells. Also, the overexpression of constitutively active AKT could offset the inhibitory effects of EG on EMT and oxidative stress in PM2.5-treated MLE-12 lung epithelial cells. Finally, AKT overexpression also blocked the inhibitory effect of EG on the phosphorylation of mTOR in PM2.5-treated MLE-12 lung epithelial cells. In conclusion, EG could improve PM2.5-induced lung fibrosis by decreasing oxidative damage and EMT through AKT/mTOR pathway, which might be a potential candidate for the treatment of PM2.5-induced lung fibrosis.